Customer Profitability Analysis in Singapore - Kapur, Sachin (2008)
As management thinking progresses and focuses more sharply on customers, it becomes relatively easier to analyze and charge cost to customers. Most valuable asset an organisation has is its customer base. Certainly no business can exist without customer and unless the customers generate revenue in excess of the costs of serving them, at least in the aggregate, then only the business will survive very long. Organisations recognize that though ÃÂÃÂ¢ÃÂÃÂÃÂÃÂexceeding customer expectationsÃÂÃÂ¢ÃÂÃÂÃÂÃÂ is a worthy goal, exceeding those expectations profitably is necessary for long-term corporate viability.